Kebijakan Pengembangan Produk Perbankan Syariah - Muaidi; Mujiatun Ridawati (STIS DAFA MATARAM, 2022)
This study analyses the policies for developing Islamic banking in Indonesia by examining its history, prospects, supporting regulations, and comparisons with Islamic banking in Malaysia. The research employs a library research method, reviewing various written sources such as books, scholarly articles, academic journals, legislation, and official reports. The data were analyzed descriptively and qualitatively to understand the development, challenges, and opportunities in advancing Islamic banking in Indonesia. The findings indicate that the prospects for Islamic banking in Indonesia are highly promising in supporting the national economy. However, more autonomous and comprehensive regulations are needed to govern this sector effectively, including innovative policies from Bank Indonesia regarding supervision and development. Furthermore, specific regulations related to Islamic bonds, Islamic capital markets, and Islamic civil law are urgently required to strengthen the Islamic banking ecosystem. This study contributes strategic recommendations to establish a regulatory framework that supports the competitive and sustainable growth of Islamic banking in Indonesia.